2019
DOI: 10.1080/09585192.2019.1620307
|View full text |Cite
|
Sign up to set email alerts
|

The gender pay gap in European executive boards: the role of executives’ pathway into the board

Abstract: We provide crosscountry evidence on the gender pay gap on executive boards in large European companies and show that the pathway into the boardinternal promotion versus external recruitmentmatters for the size of the gap. We find evidence that among executives, women are paid less than menespecially when they were recruited from outside. Since for external candidates, gender stereotyping, and discrimination might be more pronounced than for internal candidates, our results support a power-and-discrimination-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…For example, Gupta et al (2019) found that high‐growth and profit‐maximizing entrepreneurs are perceived to possess characteristics typical of men, consistent with the “think manager, think male” aphorism. Schneider et al (2019) showed, in a cross‐country setting, that female executives are paid less than male executives, with the differences more pronounced among external executive candidates. These authors argue that, despite female executives being in high demand, women are paid less because of stereotyping against female executives.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Gupta et al (2019) found that high‐growth and profit‐maximizing entrepreneurs are perceived to possess characteristics typical of men, consistent with the “think manager, think male” aphorism. Schneider et al (2019) showed, in a cross‐country setting, that female executives are paid less than male executives, with the differences more pronounced among external executive candidates. These authors argue that, despite female executives being in high demand, women are paid less because of stereotyping against female executives.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…This "role congruity" bias (Eagly & Karau, 2002) is captured in Schein's "think manager, think male" aphorism (Schein et al, 1996), whereby characteristics associated with being male align with those that people associate with a manager but no so in the case of being female. Such gender stereotyping (Gupta, Wieland, & Turban, 2019;Schneider, Iseke, & Pull, 2019) leads to biases that manifest in the contributions of female directors being discounted or subject to reactive devaluation, solely owing to their gender (Ross & Stillinger, 1991). Female directors consequently find it difficult to be effective in influencing the prevailing social norms of the board and hence the board's decisions: they are not given a hearing.…”
Section: Influences Of Female Directorsmentioning
confidence: 99%
“…International studies also confirm that a gender pay gap exists in executive boards. A recently published paper by Schneider et al (2021) revealed a gender pay gap for the boards of major European companies and indicates that external recruitment of women to the board is significant to the extent of the pay gap. The authors attribute this to gender stereotyping and discrimination, which are more pronounced in the case of external appointments.…”
Section: Research Context State Of Research and Research Gapmentioning
confidence: 99%
“…In addition to this, the dummy variable External shows whether someone previously worked in another company or was appointed to the board within the company. The variable compares board members who have gained experience within the company with those who have qualified for the board through their experience in other companies (Schneider et al 2021). To record the work experience outside the board, I include the variable Age since the length of professional experience (in prior positions) correlates closely with age.…”
Section: Control Variablesmentioning
confidence: 99%
“…Building on solid research methods with two independent samples of different employees (nursing, call centre), the paper provides a novel examination of workplace loneliness, highlighting an overlooked area of HRM. The other 'Highly Commended' paper is authored by Schneider et al (2019): 'The gender pay gap in European executive boards: the role of executives' pathway into the board'. The Committee believes that the study focuses on an important topic and has a novel take on a wellresearched problem.…”
Section: Addressing Fundamental Human Challengesmentioning
confidence: 99%